Laminate, packaging bag and package
The laminate using recycled PET films with specific crystallinity indices addresses the strength issues of recycled PET films, ensuring high puncture strength and integrity in packaging applications.
Patent Information
- Application Number
- JP2023109862
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
AI Technical Summary
Recycled PET films exhibit lower puncture strength due to changes in molecular crystal orientation and increased amorphousness, posing concerns for packaging applications.
A laminate is developed using a base film made from mechanically or chemically recycled polyethylene terephthalate (PET) films, with a crystallinity index of 18.10 or more for MR-PET and 29.00 or more for CR-PET, as measured by X-ray diffraction, to enhance puncture strength.
The laminate achieves high puncture strength, effectively preventing hole formation and quality deterioration in packaging bags, suitable for contents requiring high hygiene.
Smart Images

Figure 2025008028000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate, a packaging bag, and a packaging body. [Background technology]
[0002] Packaging bags including a laminate with a base material of recycled polyethylene terephthalate (PET) are environmentally friendly packaging bags, and their active use is expected. For example, Patent Document 1 discloses a laminate and packaging bag in which a recycled PET layer used as a base material of the laminate contains Sb and Ge, and the exothermic peak of crystallization by DSC is set to 140°C or less, thereby mitigating the decrease in physical properties such as strength. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2023-010099 A Summary of the Invention [Problem to be solved by the invention]
[0004] Known methods for recycling PET include a mechanical recycling method in which PET is treated under high temperature and reduced pressure, and a chemical recycling method in which PET is chemically decomposed. There is concern that recycled PET films made through such recycling processes have lower puncture strength than general PET films due to changes in the orientation of molecular crystals and an increase in amorphous matter. The present disclosure provides a laminate that uses recycled PET films and has a sufficiently large puncture strength. The present disclosure also provides a packaging bag and a packaging body that include such a laminate. [Means for solving the problem]
[0005] One aspect of the present disclosure provides a laminate including a base film and a sealant layer, wherein the base film comprises a mechanically recycled polyethylene terephthalate film, and when a surface of the laminate facing the base film is measured by X-ray diffraction, I1 / I0 is 18.10 or greater, where I0 is a peak intensity value detected at 2θ of 20°, and I1 is a peak intensity value for the (100) plane of the polyethylene terephthalate.
[0006] The laminate has an I1 / I0 of 18.10 or more. The I1 / I0 is the ratio of peak intensities of PET oriented crystals and amorphous matter obtained by X-ray diffraction, and can therefore be regarded as the crystallinity index of PET. Therefore, the substrate film contains a mechanically recycled polyethylene terephthalate film (MR-PET film), and when the surface of the substrate film side of the laminate is measured by X-ray diffraction, the crystallinity index of the MR-PET film is 18.10 or more, so that a laminate having a low amorphous content and a high oriented crystal content in the MR-PET film can be obtained. Such a laminate has high puncture strength.
[0007] One aspect of the present disclosure provides a laminate comprising a base film and a sealant layer, the laminate comprising a mechanically recycled polyethylene terephthalate film as the base film, in which, when the surface is measured by X-ray diffraction, the peak intensity value detected at 2θ of 20° is I0 and the peak intensity value of the (100) plane of polyethylene terephthalate is I1, the I1 / I0 is 38.00 or more.
[0008] The laminate includes an MR-PET film having a crystallinity index of 38.00 or more as a substrate film when the surface is measured by X-ray diffraction. When the MR-PET film has a crystallinity index of 38.00 or more, an MR-PET film having less amorphous matter and more oriented crystals can be obtained. By including such an MR-PET film as a substrate film, a laminate having high puncture strength can be obtained.
[0009] One aspect of the present disclosure provides a laminate comprising a base film and a sealant layer, the base film being a chemically recycled polyethylene terephthalate film in which, when the surface is measured by X-ray diffraction, the peak intensity value detected at 2θ of 20° is I0 and the peak intensity value of the (100) plane of polyethylene terephthalate is I1, the I1 / I0 is 29.00 or more.
[0010] The laminate includes a chemically recycled polyethylene terephthalate film (CR-PET film) having a crystallinity index of 29.00 or more when the surface is measured by X-ray diffraction as a substrate film. The crystallinity index of the CR-PET film is 29.00 or more, so that a CR-PET film having little amorphous matter and many oriented crystals can be obtained. By including such a CR-PET film as a substrate film, a laminate having high puncture strength can be obtained.
[0011] One aspect of the present disclosure provides a packaging bag including the laminate. The packaging bag includes the laminate, and thereby has high puncture strength.
[0012] One aspect of the present disclosure provides a package including the above-mentioned packaging bag and an item to be contained in a container of the packaging bag. The packaging bag has the above-mentioned laminate, which can prevent holes from being formed in the packaging bag. Therefore, deterioration of the quality of the item can be sufficiently prevented. In addition, such a packaging bag has a sufficiently high puncture strength, and can therefore be used particularly preferably when the item requires high hygiene. Effect of the Invention
[0013] The present disclosure provides a laminate that uses recycled PET film and has sufficiently high puncture strength. The present disclosure also provides a packaging bag and a packaging body including such a laminate. [Brief description of the drawings]
[0014] [Figure 1]FIG. 2 is a diagram showing an example of a cross section of a laminate. [Diagram 2] FIG. 2 is a diagram showing an example of a cross section of a laminate. [Diagram 3] FIG. 1 is a diagram showing an example of a packaging bag. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, the embodiments of the present disclosure will be described. However, the following embodiments are examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents. The upper or lower limit of the numerical range specified in this specification may be replaced with any value shown in the examples. In addition, the upper and lower limit values described individually may be arbitrarily combined. Unless otherwise specified, the materials or components exemplified in this specification may be used alone or in combination of two or more types. In the description, the same elements or elements having the same functions are given the same reference numerals, and duplicated descriptions are omitted. In addition, the positional relationships such as up, down, left, and right used in the description are based on the positional relationships shown in the drawings, unless otherwise specified.
[0016] 1 is a diagram showing an example of a cross section of a laminate according to one embodiment. The laminate 100 has a sealant layer 30 on one surface of a base film 10. An adhesive layer S is interposed between the base film 10 and the sealant layer 30.
[0017] The base film 10 includes at least one selected from a mechanically recycled polyethylene terephthalate film (MR-PET film) and a chemically recycled polyethylene terephthalate film (CR-PET film). The MR-PET film can be obtained by crushing and washing polyethylene terephthalate (PET), further treating it at high temperature and reduced pressure for a certain period of time, removing impurities by melt filtration, returning it to PET resin again, and processing it into a film. The CR-PET film can be obtained by crushing and washing PET, further chemically decomposing the obtained PET raw material, returning it to PET resin again, and processing it into a film. By using the recycled PET film manufactured through these recycling processes as the base film 10, it is possible to reduce the consumption of plastic resources and the CO2 emissions during PET manufacturing, and obtain an environmentally friendly laminate 100.
[0018] The thickness of the base film 10 may be 9 to 100 μm, 9 to 25 μm, or 12 to 16 μm. The thickness of the base film 10 may be adjusted depending on the application or the desired characteristics. If the thickness is too thick, the sealing performance during packaging may decrease, and the flexibility of the package may decrease, which may cause problems during packaging. If the thickness is too thin, the package may not have sufficient stiffness, and problems such as wrinkles may easily occur during packaging.
[0019] The substrate film 10 may be a stretched film or an unstretched film. It is believed that the orientation of crystals in a polymer film is improved by stretching the film. Therefore, it is preferable to use a stretched film from the viewpoint of increasing the oriented crystals in the film and improving the puncture strength. The stretching direction may be the MD direction or the TD direction. In addition, the stretching method may be any method such as uniaxial stretching or biaxial stretching, as long as it can provide a film with stable dimensions.
[0020] The sealant layer 30 is a layer that imparts heat-sealing properties to the laminate 100. Examples of components of the sealant layer 30 include thermoplastic resins, and specifically, polyolefin resins such as low-density polyethylene (LDPE), medium-density polyethylene (MDPE), linear low-density polyethylene (LLDPE), ethylene-vinyl acetate copolymer (EVA), and ethylene-α-olefin copolymers, ethylene resins such as ethylene-(meth)acrylic acid copolymers, blends of polyethylene and polybutene, homopolypropylene resin (PP), propylene-ethylene random copolymers, propylene-ethylene block copolymers, and polypropylene resins such as propylene-α-olefin copolymers, and the like can be used. In addition, a mixture of a plurality of these thermoplastic resins may be used. These thermoplastic resins can be appropriately selected depending on the intended use.
[0021] The resin constituting the sealant layer 30 may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, and a tackifier.
[0022] The thickness of the sealant layer 30 is determined depending on the weight of the contents or the shape of the packaging bag, but is preferably about 10 to 100 μm.
[0023] An adhesive layer S is interposed between the base film 10 and the sealant layer 30. Examples of adhesive materials that can be used include polyester-isocyanate resins, urethane resins, and polyether resins. By interposing the adhesive layer S, the base film 10 and the sealant layer 30 can be bonded more firmly.
[0024] The thickness of the adhesive layer S is not particularly limited and may be, for example, 0.5 to 5 μm, or 2 to 3 μm. When the thickness of the adhesive layer S is 0.5 μm or more, the adhesion between the base film 10 and the sealant layer 30 can be improved, and when it is 5 μm or less, the recyclability of the laminate 100 can be improved.
[0025] The laminate 100 can be formed by any of the known lamination methods, such as a dry lamination method in which a film-like sealant layer 30 made of the above-mentioned thermoplastic resin is laminated on the base film 10 with an adhesive such as a one-component curing or two-component curing urethane adhesive, a non-solvent dry lamination method in which a film-like sealant layer 30 is laminated using a solvent-free adhesive, and an extrusion lamination method in which the above-mentioned thermoplastic resin is heated and melted, extruded in a curtain shape, and laminated. The adhesive used to laminate the sealant layer 30 on the base film 10 forms an adhesive layer S as shown in FIG. 1. The sealant layer 30 may be directly laminated on the base film 10 without the adhesive layer S.
[0026] A printing layer can be provided on the surface of the base film 10 on the side of the sealant layer 30. The printing layer is provided at a position visible from the outside of the laminate for the purpose of displaying information about the contents, identifying the contents, or improving the design of the packaging bag. The printing method and printing ink are not particularly limited, and are appropriately selected from known printing methods and printing inks in consideration of printability on the film, design such as color tone, adhesion, safety as a food container, and the like. Examples of printing methods that can be used include gravure printing, offset printing, gravure offset printing, flexographic printing, and inkjet printing. From the viewpoints of productivity and high definition of the image, gravure printing is preferred.
[0027] In order to improve the adhesion of the printed layer, the surface of the base film 10 on the printed layer side may be subjected to various pretreatments such as corona treatment, plasma treatment, and frame treatment, or a coating layer such as an easy-adhesion layer may be provided.
[0028] Fig. 2 is a diagram showing an example of a cross section of a laminate according to another embodiment of the present disclosure. As shown in Fig. 2, the laminate 101 includes an intermediate layer 20 between the base film 10 and the sealant layer 30. The configuration of the intermediate layer 20 can be appropriately referred to the contents described above regarding the configuration of the sealant layer 30. By including the intermediate layer 20 in the laminate 101, deformation of the laminate during the manufacture of a packaging bag can be further reduced. A plurality of intermediate layers 20 may be used depending on the application of the laminate 101.
[0029] As shown in Fig. 2, a metal layer 40 may be laminated between the intermediate layer 20 and the sealant layer 30. The metal layer 40 may be laminated between the base film 10 and the intermediate layer 20, taking into consideration the manufacturing conditions. By providing the laminate 101 with the metal layer 40, the puncture strength and gas barrier properties of the laminate can be improved. In addition, the metal layer 40 may be vapor-deposited on the intermediate layer 20 in advance.
[0030] An anchor coat layer may be provided adjacent to at least one selected from the printed layer and the metal layer 40. By providing the anchor coat layer, the adhesion of the printed layer or the metal layer 40 can be increased, and the puncture strength of the laminate 100, 101 can be further improved. The anchor coat layer can be formed by applying an anchor coat agent onto a predetermined layer and drying it. For example, polyester-based polyurethane resin, polyether-based polyurethane resin, etc. can be used as the anchor coat agent. The thickness of the anchor coat layer is not particularly limited, but may be 0.1 to 1 μm, or 0.3 to 0.5 μm.
[0031] As the metal layer 40, a known metal foil such as copper foil or aluminum foil can be used. From the viewpoint of improving the gas barrier property or preventing the transmission of visible light and ultraviolet light, it is preferable to use aluminum foil. The thickness of the metal layer 40 may be, for example, 6 to 9 μm. By making the thickness of the metal layer 40 6 μm or more, the puncture strength of the laminate 100 is improved. Therefore, even if a foreign matter adheres to the base film 10 in a package including the laminate 101, the foreign matter can be prevented from appearing on the inner side of the base film 10. Therefore, deterioration of the quality of the contained contents can be suppressed.
[0032] X-ray diffraction measurement is performed on the surface x (surface of the base film 10) of the laminate 100, 101 on the side of the base film 10, and a peak pattern showing the crystalline state of the PET film can be obtained. When the base film 10 in the laminate 100, 101 includes an MR-PET film, among the peaks obtained by X-ray diffraction measurement, the peak intensity value of the halo peak (diffraction line derived from amorphous material) detected at 2θ of 20° is I0, and the peak intensity value of the (100) plane of PET is I1, and I1 / I0 is 18.10 or more. The measurement can be performed, for example, using an X-ray diffraction device (RINT ULTIMA III, manufactured by Rigaku Corporation) with an X-ray source of Cu-Kα radiation, a diffraction angle of 10°<2θ<40°, a voltage of 40 kV, and an output of 40 mA current. The peak intensity value indicates the height (cps) of the peak based on the baseline.
[0033] Pre-processing such as smoothing of the peak pattern obtained by X-ray diffraction measurement and background processing may be performed by a known method that is installed as standard in the X-ray diffraction device. Examples of methods for background processing of the peak pattern include the manual (spline) method and the SONNVELT-VISSEER method. In the present disclosure, the manual (spline) method is used from the viewpoint of reducing the variation in peak intensity after background processing and improving accuracy. The manual (spline) method is a method in which two 2θ positions are specified, and a spline approximation line passing through the two points is used as the background. The minimum value of the 2θ position may be 5 to 15°. The maximum value of the 2θ position may be 35 to 45°.
[0034] X-ray diffraction measurements reveal a broad halo peak at 2θ of around 20°, which is usually due to amorphous matter. The presence of such a halo peak confirms the presence of amorphous matter in the PET film. By specifying the 2θ at which the halo peak is detected as 20°, the variation in the peak intensity value (I0) of the halo peak can be suppressed.
[0035] X-ray diffraction measurements show a peak at 2θ of around 26° that is attributable to the (100) plane of PET. The presence of such a peak attributable to the (100) plane of PET confirms that there is a high proportion of crystals oriented in a specific direction in the PET. The reason for selecting the (100) plane is that the peak attributable to this crystal plane is usually the largest in stretched PET films.
[0036] Among the peaks obtained by X-ray diffraction, the method of specifying the halo peak (2θ=20°) with a peak intensity value of I0 is performed manually using the analysis software attached to the X-ray diffraction device, but the peak of the PET (100) plane with a peak intensity value of I1 is the peak automatically detected by peak search processing using the analysis software attached to the X-ray diffraction device.
[0037] When the peak intensity value of the above-mentioned halo peak is I0 and the peak intensity value derived from the (100) plane of PET is I1, I1 / I0 is 18.10 or more. The obtained I1 / I0 represents the ratio of oriented crystals to amorphous matter, and can be regarded as the crystallinity index of PET. Therefore, the laminates 100 and 101 having a crystallinity index of 18.10 or more have a high puncture strength due to the low ratio of amorphous matter and the high ratio of oriented crystal matter in the MR-PET film.
[0038] The crystallinity index may be 18.15 or more, or 18.20 or more. When the crystallinity index is in this range, a laminate including an MR-PET film having a lower amorphous content and a higher oriented crystal content can be obtained. Therefore, such a laminate has a higher puncture strength.
[0039] The puncture strength of the laminates 100, 101 can be measured based on "7.5 Puncture Strength Test" of JIS Z1707:2019 "General Rules for Food Packaging Plastic Films". For example, the measurement can be performed by piercing the laminates 100, 101 from the surface x on the base film 10 side toward the opposite side using a Tensilon AD-7303 (manufactured by A&D Co., Ltd.). The puncture strength of the laminates 100, 101 may be 8.5 N or more, or may be 8.6 N or more. By providing a laminate having such a puncture strength, a packaging bag and a packaging body having high puncture strength can be obtained. The puncture strength of the laminates 100, 101 may be 10.0 N or less.
[0040] The puncture strength of the base film 10 may be 7.7 N or more, or may be 7.8 N or more. The puncture strength of the base film 10 may be 9.0 N or less. By providing such a base film 10, the puncture strength of the laminates 100, 101 can be improved.
[0041] The laminates 100, 101 include the MR-PET film having the I1 / I0 of 38.00 or more as the base film 10 when the MR-PET film alone is subjected to X-ray diffraction measurement. The method for measuring the X-ray diffraction and puncture strength is as described above. By using the MR-PET film having an I1 / I0 of 38.00 or more as the base film 10, the laminates 100, 101 having high puncture strength can be obtained. In this case, from the viewpoint of further increasing the puncture strength of the laminate, the I1 / I0 may be 39.00 or more, or may be 40.00 or more.
[0042] When the base film 10 in the laminates 100, 101 is a CR-PET film, the base film 10 is a CR-PET film having an I1 / I0 of 29.00 or more when the CR-PET film alone is subjected to X-ray diffraction measurement. The method for measuring the X-ray diffraction and puncture strength is as described above. By using a CR-PET film having an I1 / I0 of 29.00 or more as the base film 10, the laminates 100, 101 having high puncture strength can be obtained. In this case, from the viewpoint of further increasing the puncture strength of the laminate, the I1 / I0 may be 31.00 or more, or may be 33.00 or more.
[0043] 3 is an example of a packaging bag formed using a laminate. The packaging bag 200 includes a sealed portion 211 formed by bonding together the peripheries of a pair of substantially rectangular laminates 100, and a storage portion 218 formed between the pair of laminates 100, 100 by the sealed portion 211. That is, the packaging bag 200 has a side end portion 214, a lower end portion 216, and an upper end portion 217 sealed by the sealed portion 211. The packaging bag 200 includes a storage portion 218 in which an object such as food is stored, in a non-sealed portion 215 surrounded by the sealed portion 211. The object such as food is enclosed in the storage portion 218. The sealed portion 211 at the lower end portion 216 may be sealed after the object is filled in the storage portion 218.
[0044] The pair of laminates 100 are overlapped with the sealant layers 30 facing each other. The pair of laminates 100 may be bonded to each other at the seal portion 211 by an adhesive. The pair of laminates 100 may form the seal portion 211 by bonding the heat seal layers provided on the sealant layers 30 to each other.
[0045] Since the laminate 100 has a high puncture strength, it is possible to sufficiently prevent deterioration of the contents contained in the storage section 218 due to the inflow of trace components, PET components, or outside air mixed in during the recycling process through holes formed by puncture. The packaging bag 200 may have an optional layer on the base film 10 and the sealant layer 30 of the laminate 100.
[0046] The procedure for manufacturing a packaging bag 200 (packaging body) using the laminate 100 is described below. A pair of laminates 100 is prepared. In the case of the laminate 100, the sealant layers 30 of the laminates 100 are placed opposite each other, and the sealant layers 30 are bonded together with, for example, a fastener tape interposed therebetween, which serves as the resealing means 230. This forms sealed portions 211 at positions corresponding to the upper end 217 and the side ends 214, 214, and forms a non-sealed portion 215 surrounded by the sealed portions 211 in a U-shape.
[0047] After the sealing portion 211 is formed, the opening means 220 may be formed. For example, the side end portions 214, 214 are formed with easy-to-open processed portions 224, 224 consisting of a group of scars. The easy-to-open processed portions 224 are not limited to a group of scars, and may be V-shaped, U-shaped, I-shaped or other notches. In addition, a half-cut line 221 that serves as a trajectory for cutting from the easy-to-open processed portion 224 may be formed on the surface portion of the laminate 100 between the upper end portion 217 and the resealing means 230. The half-cut line 221 can be formed using a laser beam. After the opening means 220 is formed, the sealing portion 211 is cut and trimmed to separate the package into individual packaging bags.
[0048] Next, the contents are filled from the unsealed lower end 216. Thereafter, the laminates 100 are bonded together at the lower end 216, and a seal portion 211 is also formed at the lower end 216. In this manner, the packaging bag 200 and the package can be manufactured. The half-cut line may be formed before the pair of laminates 100 that have been bonded together are slit to a predetermined width.
[0049] The packaging bag 200 is provided with opening means 220 at the upper end side of the non-sealed portion 215 for cutting open the side ends 214, 214 of the packaging bag 200 and across the space therebetween to open the bag, and resealing means 230 below the opening means 220 for resealing the storage portion 218 after the bag is opened by the opening means 220. The resealing means 230 may appropriately adopt a known structure capable of repeatedly opening and sealing. For example, the resealing means 230 may be a synthetic resin fastener capable of repeatedly sealing by fitting a strip-shaped protrusion into a strip-shaped groove, or may be an adhesive seal.
[0050] The package includes a packaging bag 200 and an object contained in the container 218 of the packaging bag 200. Examples of the object include food, electronic materials, and electronic devices. The package includes the packaging bag 200, and therefore has high puncture strength, and can prevent the object from being altered or deteriorated by a hole formed by puncture that allows trace components, PET components, or outside air mixed in during the recycling process to flow in. Therefore, a recycled PET film can be used as the packaging bag, and therefore a package that is environmentally friendly and has improved puncture strength can be provided.
[0051] Although several embodiments of the present disclosure have been described above, the present disclosure is not limited to the above embodiments. For example, the laminate 100 and the laminate 101 used in the above description may be appropriately replaced with each other. The laminates 100 and 101 may have any layer or thin film between the base film 10 and the sealant layer 30, between the base film 10 and the intermediate layer 20, or between the intermediate layer 20 and the sealant layer 30, as long as the function of the laminate is not significantly impaired. The shape of the packaging bag 200 and the packaging body is not limited to a four-sided bag. For example, it may be a two-sided bag, a three-sided bag, or a palm-shaped bag, or it may be a standing pouch shape with a bottom tape added.
[0052] The present disclosure includes the following contents. [1] A laminate comprising a base film and a sealant layer, The substrate film comprises a mechanically recycled polyethylene terephthalate film; A laminate, wherein, when the surface of the laminate on the base film side is measured by X-ray diffraction, I1 / I0 is 18.10 or more, where I0 is the peak intensity value detected at 2θ of 20°, and I1 is the peak intensity value of the (100) plane of polyethylene terephthalate. [2] A laminate comprising a base film and a sealant layer, The laminate comprises, as the base film, a mechanically recycled polyethylene terephthalate film having an I1 / I0 ratio of 38.00 or more when the surface is measured by X-ray diffraction, where I0 is the peak intensity value detected at 2θ of 20° and I1 is the peak intensity value of the (100) plane of polyethylene terephthalate. [3] A laminate comprising a base film and a sealant layer, The laminate comprises, as the base film, a chemically recycled polyethylene terephthalate film having an I1 / I0 ratio of 29.00 or more when the surface is measured by X-ray diffraction, where I0 is the peak intensity value detected at 2θ of 20° and I1 is the peak intensity value of the (100) plane of polyethylene terephthalate. [4] The laminate according to [3], wherein the chemically recycled polyethylene terephthalate film has a thickness of 9 to 100 μm. [5] The laminate according to [1] or [2], wherein the mechanically recycled polyethylene terephthalate film has a thickness of 9 to 100 μm. [6] The laminate according to any one of [1] to [5], which has a puncture strength of 8.5 N or more. [7] A packaging bag comprising the laminate according to any one of [1] to [6] above. [8] A packaging body comprising the packaging bag described in [7] above and an item contained in the storage section of the packaging bag. EXAMPLES
[0053] The present disclosure will be described in more detail below with reference to examples, comparative examples, and reference examples. Note that the present disclosure is not limited to the following examples.
[0054] [Measurement of the crystallinity index of polyethylene terephthalate (PET) film] (Examples 1 to 6, Comparative Examples 1 to 4, Reference Examples 1 to 10) We prepared a commercially available mechanically recycled PET film (MR-PET film), a commercially available chemically recycled PET film (CR-PET film), and a commercially available PET film that had not been recycled (general PET film). Two types of general PET film from different manufacturers were prepared, and were named general PET film A and general PET film B. The thickness of each film was 12 μm.
[0055] Each PET film was cut into five sample pieces of 4.8 cm x 4.8 cm each. The obtained sample pieces were measured under the following conditions using a RINT ULTIMA III (Rigaku Corporation). Since it was confirmed that there were no diffraction lines originating from the sample due to Cu-Kβ rays, a Ni filter was not used to prevent a decrease in the intensity of the diffraction lines originating from the sample due to Cu-Kα rays.
[0056] ·X-ray source: Cu-Kα Voltage: 40kV ·Current: 40mA Scan method: 2θ-θ method (parallel beam method) Counting unit: cps Scanning speed: 4° / min Measurement range: 10°<2θ<40° Sampling speed: 0.020° / min -Sample stage control mode: Rotation Ni filter: Not used
[0057] The peak pattern of each PET film obtained was subjected to a leveling process at 19 points, and two points, 2θ=10° and 2θ=40°, were selected, and background processing was performed between the two points by the manual (spline) method. From the peak pattern after processing, the peak intensity value at 2θ=20° was set as I0, and the peak intensity value derived from the (100) plane of PET occurring at 2θ around 26° was set as I1, and the crystallinity index of each sample piece represented by I1 / I0 was calculated. The results obtained are shown in Table 1. In addition, for MR-PET films, those with a crystallinity index of 38.00 or more were set as examples, and those with a crystallinity index of less than 38.00 were set as comparative examples, and the average value was calculated for each example and comparative example. For CR-PET films, those with a crystallinity index of 29.00 or more were set as examples, and the average value of the examples was calculated. The calculated average values are shown in Table 1.
[0058] [PET film puncture strength measurement] The puncture strength of the sample pieces subjected to the above X-ray measurement was measured under the following conditions based on "7.5 Puncture Strength Test" of JIS Z1707:2019 "General Rules for Food Packaging Plastic Films". The measurement device used was Tensilon AD-7703 (manufactured by A&D Co., Ltd.). The results are shown in Table 1. In addition, the average values of the examples and comparative examples of each PET film were calculated using the same procedure as for the crystallinity index, and the calculated average values are also shown in Table 1.
[0059] Test speed: 50mm / min Load cell: 100N Load range: 10N (10%)
[0060] [Table 1]
[0061] As shown in Table 1, each recycled PET film tended to have a lower puncture strength than general PET films. It is believed that recycled PET films have lower strength than general PET films because they are made through the PET recycling process. Here, we investigated the relationship between the crystallinity index and puncture strength of each PET film, and found that the higher the crystallinity index, the higher the puncture strength. Therefore, it is believed that by using recycled PET films with high crystallinity indexes as the base film of a laminate, a laminate with the same puncture strength as that of a general PET film can be obtained. The crystallinity index of PET films with high puncture strength also differs depending on the type of recycled PET film, and it was confirmed that recycled PET films with particularly high puncture strength can be obtained when the crystallinity index is 38.00 or more in the case of MR-PET films and 29.00 or more in the case of CR-PET films.
[0062] [Laminated body production] (Examples 7 to 9, Comparative Examples 5 and 6) A laminate was produced using the MR-PET film (MR-PET) used in Example 1 as a substrate film by the following procedure. A printed layer was formed on one side of the substrate film. An anchor coating agent containing a polyester-based polyurethane resin was applied to the printed layer to form a first anchor coating layer (AC1) with a thickness of 0.5 μm.
[0063] A polyethylene film (PE1, thickness: 15 μm) was attached onto the first anchor coat layer by extrusion lamination, and aluminum foil (thickness: 7 μm) was further vapor-deposited onto the polyethylene film. An anchor coating agent was applied onto the vapor-deposited aluminum foil to form a second anchor coat layer (AC2) with a thickness of 0.5 μm.
[0064] A polyethylene film (PE2, thickness: 25 μm) was bonded as a sealant layer onto the second anchor coat layer by extrusion lamination. In this way, a laminate was produced. The produced laminate was cut into five sample pieces of 4.8 cm × 4.8 cm.
[0065] The layer structure in this example is as follows. MR-PET / Printing layer / AC1 / Adhesive layer / PE1 / Aluminum foil / AC2 / Adhesive layer / PE2
[0066] (Reference examples 11~15) Except for using the general PET film A as the base film instead of the MR-PET film, a laminate was produced in the same manner as in Example 7. The produced laminate was cut into five sample pieces of 4.8 cm x 4.8 cm.
[0067] [Measurement of crystallinity index and puncture strength of laminate] X-ray diffraction measurement was performed on the surface of the substrate film side of the sample piece of the laminate, and the crystallinity index was calculated. The conditions for the X-ray measurement were as described above. In addition, the puncture strength was measured by piercing a needle into the surface of the substrate film side of the laminate on which the X-ray measurement was performed. The method for measuring the puncture strength was as described above. The measurement results are shown in Table 2. In laminates using an MR-PET film as the substrate film, those with a crystallinity index of 18.10 or more were classified as examples, and those with a crystallinity index of less than 18.10 were classified as comparative examples. The average values for the examples and comparative examples are also shown in Table 2.
[0068] [Table 2]
[0069] As shown in Table 2, similar to the tendency of the PET film alone, the puncture strength also tended to increase with an increase in the crystallinity index in the case of the laminate. Compared with Table 1, it was confirmed that the laminate had a higher puncture strength than the PET film alone. Furthermore, the puncture strength of the laminate when the crystallinity index of the laminate using the MR-PET film was 18.10 or more was higher than that of Reference Example 15, which had the lowest puncture strength among Reference Examples 11 to 15, which used the general PET film A. Therefore, it was shown that the laminate using the MR-PET film as the base film and having a crystallinity index of 18.10 or more has a high puncture strength equivalent to that of the laminate using the general PET film A. From this result, it was confirmed that the puncture strength of the recycled PET film alone was low, but the puncture strength of the laminate including the recycled PET film whose crystallinity index exceeded the threshold value was greatly improved, and showed a puncture strength equivalent to that of the laminate using the general PET film A. Therefore, it was shown that a packaging bag and a packaging body with high strength can be produced using an environmentally friendly recycled PET film. [Industrial Applicability]
[0070] According to the present disclosure, it is possible to provide a laminate having a sufficiently high puncture strength while using a recycled PET film, and also to provide a packaging bag and a packaging body using such a laminate. [Explanation of symbols]
[0071] 10...base film, 20...intermediate layer, 30...sealant layer, 40...metal layer, 100, 101...laminate, S...adhesive layer, x...surface, 200...packaging bag, 211...sealed portion, 214...side end, 215...unsealed portion, 216...lower end, 217...upper end, 218...container portion, 220...opening means, 221...half-cut line, 224...easy-open processing portion, 230...resealing means.
Claims
1. A laminate comprising a base film and a sealant layer, The substrate film comprises a mechanically recycled polyethylene terephthalate film; A laminate, wherein, when a surface of the laminate on the base film side is measured by X-ray diffraction, I1 / I0 is 18.10 or more, where I0 is a peak intensity value detected at 2θ of 20°, and I1 is a peak intensity value of a (100) plane of polyethylene terephthalate.
2. A laminate comprising a base film and a sealant layer, The laminate comprises, as the base film, a mechanically recycled polyethylene terephthalate film having an I1 / I0 ratio of 38.00 or more when the surface is measured by X-ray diffraction, where I0 is the peak intensity value detected at 2θ of 20° and I1 is the peak intensity value of the (100) plane of polyethylene terephthalate.
3. A laminate comprising a base film and a sealant layer, The laminate comprises, as the base film, a chemically recycled polyethylene terephthalate film in which, when the surface is measured by X-ray diffraction, the peak intensity value detected at 2θ of 20° is I0 and the peak intensity value of the (100) plane of polyethylene terephthalate is I1, the I1 / I0 ratio is 29.00 or more.
4. The laminate according to claim 3, wherein the chemically recycled polyethylene terephthalate film has a thickness of 9 to 100 μm.
5. The laminate according to claim 1 or 2, wherein the mechanically recycled polyethylene terephthalate film has a thickness of 9 to 100 μm.
6. The laminate according to any one of claims 1 to 4, having a puncture strength of 8.5 N or more.
7. A packaging bag comprising the laminate according to any one of claims 1 to 4.
8. A package comprising the packaging bag according to claim 7 and an item contained in the container of the packaging bag.
Citation Information
Patent Citations
Laminated film and packaging bag
JP2023010099A